n형 Mg3Sb2-xBix 열전소재의 오믹접합층 형성을 위한 고상접합기술 - 주성재; 장정인; 손지희; 박종호; 김봉서; 민복기 (대한금속·재료학회지, 63(1), 2025)
N-type Mg3Sb2-xBix materials are expected to replace n-type bismuth telluride because they are moreabundant in the Earth's crust and lower in cost. However, the metallization process of this material, whichis essential to develop modules, has been relatively under-researched. According to the literature, one-stepsintering process based on powder metallurgy is mostly used to form an ohmic bonding layer on n-type Mg3Sb2-xBix materials. However, this method is not reproducible nor practical, and is unsuitable for industrial massproduction. This paper presents a new, simple method for metallization, the solid-state direct bonding of Mgand Cu foils on sintered n-type Mg3Sb2-xBix. It employs interdiffusion between the thermoelectric material andthe metal layer at elevated temperatures to form a tight and robust bond. Mg was chosen as the contact metalso that the interdiffusion of Mg would not cause a Mg deficiency in the Mg3Sb2-xBix near the interface. Then,a Cu layer was selected as the second metal to wrap around the Mg layer so that the subsequent solderingprocess could be the same as that of bismuth telluride. Solid-state bonding with the Mg/Cu double layerformed a structurally perfect joint at 723 K. When the temperature of the solid-state bonding exceeded750 K, the eutectic point of Mg and Cu, the Mg layer was lost due to liquid phase formation. Solid-phasebonding at 723 K produced no noticeable change in the Seebeck coefficient near the interface, whichwould be caused by the outdiffusion of Mg from the n-Mg3Sb2-xBix. The specific contact resistance wasabout 53.8 μΩ cm2. This is superior to the values reported for n-type Bi2Te3-based materials. In this study,we also fabricated a Mg3Sb2-xBix (n)-Bi2Te3 (p) hybrid thermoelectric module and evaluated the outputcharacteristics, which confirmed the high applicability of our solid-state bonding process. KCI Citation Count: 0